Pemanfaatan Aplikasi Keuangan Digital untuk Mewujudkan UKM Handal - Juwita Sari; Titik Mildawati; Yahya Yahya; Kurnia Kurnia (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2022)
The government's program "Belanja di Warung Tetangga" is one of the efforts to increase sales transactions at traditional grocery stores (Toko kelontong). On the other hand, with restrictions on the public's movement space due to an appeal from the government to suppress the spread of COVID-19, people's spending behavior has begun to change. If you usually shop at the supermarket, stay at home and shop at the store near your house. This shows the fact that traditional grocery store buyers have indeed declined, but sales of household goods have continued. Sales of basic commodities are still operating. Traditional Grocery stores cannot control people's purchasing power because indeed the global economic conditions are not good, but their business does not immediately close. Therefore, while surviving in the midst of a pandemic, it is possible that traditional grocery stores can streamline their operations. This STIESIA’s teams activity with traditional grocery store business partners outlines solutions to traditional grocery store problems, through financial management using the "buku warung" application. The Stiesia's teams, acts as a facilitator as well as a companion from the the traditional grocery store with the developer of the Buku Warung. The fundamental contribution of this activity is the improvement of traditional grocery stores in managing their financial effectiveness. Increasing the understanding of traditional grocery store regarding digital financial records and opening up the insight of owners on current technological developments. The hope is, during this pandemic, traditional grocery stores can survive and be able to perform financial efficiency.